As formas de organização “em rede”: configuração e instrumento de análise da dinâmica industrial recente - Mazzali, Leonel [UNESP]; Costa, Vera Mariza H. Miranda [UNESP] (Centro de Economia Política, 2022)
The transition from the 80’ s to the 90’ s points to the growing of a new pattern of industrialization and development. In this process, new forms of intra and inter firms organization develop. The purposes of this paper are to characterize the “new” form of firm organization, “network”, and to discuss the theoretical basis which support this new kind of shaping the management of the inter-dependences among the economic agents. Two main lines are identified, centered, respectively, in the allocation and in the creation of resources, that give distinct visions of the organization process and of the delimitation of the inter-relations among firms.

A transição dos anos 80 para os 90 aponta para o crescimento de um novo padrão de industrialização e desenvolvimento. Nesse processo, novas formas de organização intra e inter firmas se desenvolvem. O objetivo deste artigo é caracterizar a “nova” forma de organização das empresas, a “rede”, e discutir os fundamentos teóricos que sustentam esse novo tipo de configuração da gestão das interdependências entre os agentes econômicos. Identificam-se duas linhas principais, centradas, respetivamente, na alocação e na criação de recursos, que dão visões distintas do processo de organização e da delimitação das inter-relações entre as empresas.
Forms of network organization: configuration and instrument of analysis of the recent industrial dynamic
Keywords: Globalização; network organization; innovation; Globalização; organização em rede; inovação